IMPLEMENTASI PENDIDIKAN KARAKTER PEDULI LINGKUNGAN PADA SISWA DI SMP NEGERI 5 ABIANSEMAL - Ni Kadek Puspita Sari; Ni Wayan Arini; Kadek Dwi Sentana Putra (Yayasan Pendidikan Literasi Borneo, 2026)
This study aims to analyze the implementation of environmental care character education among students at SMP Negeri 5 Abiansemal through the Adiwiyata Program and to identify the supporting and inhibiting factors affecting its implementation. The study employed a descriptive qualitative approach using a single case study design. Research participants consisted of the principal, teachers, Adiwiyata program coordinator, and students selected through purposive sampling. Data were collected through observation, in-depth interviews, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings reveal that environmental care character education has been implemented through the integration of environmentally oriented school policies, positive habit formation, participatory activities, environmentally friendly facilities management, and the strengthening of school culture. The Adiwiyata Program serves as the primary instrument for fostering responsibility, discipline, and environmental awareness through waste segregation, classroom cleaning duties, greening activities, plant maintenance, waste bank management, and regular school clean-up programs. The school’s green physical environment, along with the commitment of school leaders, teachers, and active student participation, were identified as the main supporting factors. Conversely, variations in students’ environmental awareness and family background were found to be inhibiting factors. The study concludes that environmental care character education can be effectively developed through sustainable synergy among school policies, organizational culture, contextual learning practices, and the active involvement of all school stakeholders in fostering students’ ecological awareness